Implementation of Village Autonomy: A Normative Study of Law Number 6 of 2014 Concerning Villages - Faisal, Fatma; Attas, Nasrah Hasmiati (Journal of Legal Contemplation, 2025)
This study focuses on gaining an in-depth understanding of the implementation of village autonomy based on the legal framework of Law Number 6 of 2014 concerning Villages. This study uses a normative legal research method, also known as library legal research. This means that this study is based on searching and analyzing library materials and applicable legal provisions, then linking them to the issues being studied. The statute approach is the main analytical foundation of this research. The results of this research explain that Law Number 6 of 2014 concerning Villages is indeed an important milestone designed to strengthen decentralization and autonomy at the village level in Indonesia. Conceptually, this law gives villages broader authority in managing resources and making strategic decisions. However, in practice, the implementation of village autonomy still faces a series of complex obstacles. Significant obstacles identified include overlapping authorities between policies originating from the central government and local governments, as well as legal ambiguities that cause uncertainty at the village level. Overcoming these challenges is essential to ensure that village autonomy can operate effectively and efficiently.